Analysis of Herding Behavior During The Covid-19 Pandemic And Russia’s Invasion of Ukraine - Abyuda, Gede Satya Wicaksana; Lubis, Arief Wibisono (Eduvest - Journal of Universal Studies, 2025)
The energy sector plays a crucial role in the global economy but is vulnerable to economic crises, pandemics, and geopolitical conflicts that trigger stock price volatility. This study investigates herding behavior among investors during two major crises, namely the COVID-19 pandemic and the Russia-Ukraine invasion, focusing on energy sector stocks listed on the Indonesia Stock Exchange (IDX) from 2018 to 2022. The study aims to identify indications of herding behavior in energy sector stock returns during these crisis periods. A quantitative approach was employed, analyzing daily time series data. The sample consisted of 57 stocks selected using the purposive sampling method based on relevant criteria. Hypothesis testing was conducted to identify differences in herding behavior across the two crisis periods and to evaluate the impact of West Texas Intermediate (WTI) crude oil price fluctuations on herding behavior in the energy sector. The findings reveal indications of herding behavior in energy sector companies during the 2018–2022 period. However, there is no strong evidence to support the occurrence of herding behavior during the COVID-19 pandemic and the Russia-Ukraine invasion. Furthermore, WTI crude oil price fluctuations were not found to significantly influence herding behavior in the energy sector. These findings are expected to serve as a reference for regulators and academics in designing more effective policies to manage market behavior during periods of global uncertainty and to encourage further research exploring other factors influencing herding behavior across various sectors.